Sources of Mortality on Dialysis with an Emphasis on Microemboli. Issue 6 (16th August 2016) - Stegmayr, Bernd G.
Abstract: Patients on chronic hemodialysis have a shortened survival compared to the general population. There are multiple sources of morbidity and mortality unique to the dialysis population that account for this. Reasons include the effects of blood membrane interactions, intradialytic hypotension, myocardial stunning, excessive interdialytic weight gain, high‐flow arteriovenous fistulae, and impaired lipid break down by anticoagulation administered during HD. Another risk factor, not well appreciated, is the occurrence of microemboli of air (microbubbles) during HD. Such microemboli are not effectively removed by the venous air trap and the safety system provides no warning when these small microbubbles enter the venous bloodline of the extra corporeal circuit and then the venous circulation of the patient. Data indicate that the gas emboli are not fully adsorbed and become embedded by fibrin resulting in a combined clot that causes microemboli in the lung. In addition, these microbubbles (of the size of blood corpuscles) can pass the pulmonary circulation into the left heart and then into the general arterial circulation explaining their detection not only in the lungs but also in the brain and heart of patients. Risk factors for such microbubble appearance include the high blood pump speed associated with high‐efficiency dialyses. This review will discuss these various issues in relation to the better outcome of patients in Japan and also how to reduce some of these risk factors.